2008
DOI: 10.1038/sc.2008.104
|View full text |Cite
|
Sign up to set email alerts
|

Physiatrists' opinions and practice patterns for bone health after SCI

Abstract: Study design: Self-report survey Objective: To ascertain physiatrists' opinions and current practice patterns for bone health management after spinal cord injury (SCI). Participants: Physiatrists who work in teaching rehabilitation centers in Canada. Methods: A 4-page 17-question survey (available in French and English) was sent to working physiatrists in all major Canadian SCI rehabilitation centers. Results: We had an 85% response rate (22 responses). Physiatrists reported that they should be managing bone h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Despite self-reported bone health screening practices between 54% and 82% 22,23 among health care providers, a recent retrospective review of postfracture care across 4 Veterans Affairs Medical Centers in the United States revealed that less than 5% of individuals with SCI had a DXA scan in the year before or after fracture. 6 The lack of proper screening practices and awareness among health care providers suggests that current practices are likely failing to identify persons at high risk of fracture, thereby limiting the ability to prevent fracture occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Despite self-reported bone health screening practices between 54% and 82% 22,23 among health care providers, a recent retrospective review of postfracture care across 4 Veterans Affairs Medical Centers in the United States revealed that less than 5% of individuals with SCI had a DXA scan in the year before or after fracture. 6 The lack of proper screening practices and awareness among health care providers suggests that current practices are likely failing to identify persons at high risk of fracture, thereby limiting the ability to prevent fracture occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no consensus on a systematic approach to the management of sublesional bone loss and fracture after SCI. Spinal injuries physicians typically have a reactive response to fracture, rather than implementing proactive management [10]. Early identification of individuals at highest risk of fracture may allow targeted preventative treatment, which would ideally begin during their inpatient stay in their primary care or rehabilitation unit.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, individuals living with SCI report daytime symptoms such as fatigue, excessive day time sleepiness,11,12 difficulties with concentration, and impaired quality of life. Furthermore, fatigue and excessive daytime sleepiness, have been associated with pain,13 depression,14 side effects of medications, spasticity,15 discomforts related to posture16 and autonomic dysfunction17 in people living with SCI. Intrestingly, recent studies suggested that SCI does not in itself result in significantly impact of fatigue on health-related quality of life 18.…”
Section: Introductionmentioning
confidence: 99%